Control interno en las cuentas por pagar de la distribuidora Touma S.A. Ditosa de la ciudad de Babahoyo, periodo 2020 – 2021. - Obando Vera, Ariel Alfredo (2023)
Having an efficient internal control system in the accounts payable area is crucial for ensuring reliability and effectiveness in financial management of companies. The lack of a clearly defined process for managing current and non-current accounts payable in most companies makes it difficult to implement activities such as timely bank reconciliation and financial statement preparation. It is important to note that internal control is essential to ensure the reliability and accuracy of the financial and accounting information of the company. The investigation will analyze existing policies and processes, identify factors contributing to inefficiencies in accounts payable management, and propose specific recommendations to strengthen internal control in this critical area. This will help improve financial management, optimize resources, and ensure sustainability. A combined methodology of quantitative and qualitative approaches was used. The quantitative methodology allowed for analysis of quantifiable variables, while the qualitative approach focused on context and structural situations. The deductive method was applied to study the activities and administrative processes of the company and obtain as much information as possible. A descriptive investigation was conducted and interviews were conducted with the company representative to obtain precise and detailed information. A combination of quantitative and qualitative methods were used to obtain a complete picture of the company's accounts payable situation.